Shish-Kebab Nanohydroxyapatite-TiO₂ Nanofiber: A Biomimetic Platform for Regenerative Medicine - Pandeya, Shiva; Sah, Shiv Kumar; Li, Ziliang; Joshi, Mahesh Kumar (Journal of Nepal Chemical Society, 2025)
Flexible titanium dioxide (TiO₂) nanofibers are gaining considerable attention in bone tissue engineering owing to their superior biocompatibility, extensive surface area, and structural adaptability. This study explores the synthesis of flexible TiO2 nanofibers and its in vitro evaluation for biomineralization capability. The Flexible TiO2 NFM was fabricated employing electrospinning technique followed by controlled calcination. The SEM-EDS, TEM, XRD, and FTIR analysis were done to characterize and to confirm the biomineralization of the flexible TiO2 NFM.  Surface analysis via scanning electron microscopy (SEM) revealed the progressive formation of apatite-like layers. Elemental confirmation was provided by energy-dispersive X-ray spectroscopy (EDS), which identified the presence of calcium (Ca) and phosphorus (P), with Ca/P ratios nearing the ideal value for stoichiometric hydroxyapatite (~1.64). EDS spectra displayed characteristic peaks for oxygen at~0.52 keV, calcium at 3.69 keV & 4.01 keV, and phosphate 2.01 keV, confirming the deposition of calcium phosphate and the effectiveness of the biomineralization process. XRD analysis for biomineralized NFM showed distinct peaks at 2θ values of 28.5°, 31.7°, and 66.3°. Likewise FTIR analysis showed notable alterations with characteristics peaks at 3418 cm⁻¹ suggesting increased hydrophilicity, and 1625.96 cm⁻¹, 1394.55 cm⁻¹, 1034.65 cm⁻¹ for confirmation of calcium phosphate phase, such as hydroxyapatite. The presence of granular textures on the fiber surface indicated the successful formation of apatite-like structures. TEM analysis revealed a well-defined crystalline core surrounded by a biomineralized layer, closely resembling the mineral composition of natural bone. The results of XRD and FTIR peaks further confirmed the biomineralization of flexible TiO2 NFM.